Evaluating meta-analysis as a replication success measure. - Jasmine Muradchanian; Rink Hoekstra; Henk Kiers; Don van Ravenzwaaij (PLoS ONE)
Background The importance of replication in the social and behavioural sciences has been emphasized for decades. Various frequentist and Bayesian approaches have been proposed to qualify a replication study as successful or unsuccessful. One of them is meta-analysis. The focus of the present study is on the way meta-analysis functions as a replication success metric. To investigate this, original and replication studies that are part of two large-scale replication projects were used. For each original study, the probability of replication success was calculated using meta-analysis under different assumptions of the underlying population effect when replication results were unknown. The accuracy of the predicted overall replication success was evaluated once replication results became available using adjusted Brier scores. Results Our results showed that meta-analysis performed poorly when used as a replication success metric. In many cases, quantifying replication success using meta-analysis resulted in the conclusion where the replication was deemed a success regardless of the results of the replication study. Discussion We conclude that when using meta-analysis as a replication success metric, it has a relatively high probability of finding evidence in favour of a non-zero population effect even when it is zero. This behaviour largely results from the significance of the original study. Furthermore, we argue that there are fundamental reasons against using meta-analysis as a metric for replication success.